Proces twórczy – droga kształtowania tożsamości artysty - Rodziński, Stanisław (Horyzonty Wychowania, 2017)
The text is the fruit of reflection concerning artistic creation, especially of the phenomenon colloquially referred to as the creative process. People have been interested in arts for centuries, which entailed the interest in the artist himself, in his life, environment, the origin of his creative passions. When the artists began to sign their works, when they started to reveal the authorship of their creation, this interest became something natural, though today it seems – awash with gossip, it, not infrequently, exceeds the size of the work and the artist himself. Looking at the selfportraits of Rembrandt or Van Gogh – but also reading auto biographical literature – we realize that there is no work of art, no significant work of art, in which the whole range of the creator’s privacy, his times and most important issues would be discarded. In fine arts, as well as in literature, poetry, and music – encountering a piece of work – we do encounter the man. This encounter sometimes induces the search for knowledge about the artist, his methods of work, his lifestyle, dramas and joys that surrounded him. In his „Letter to the Artists”, John Paul II touched upon this problem writing that the history of art does not constitute the mere history of works of art, but it also refers to the people. In this way, we come to a point in which the knowledge of the work of art involves the knowledge of the artist.